Social intervention program for observation and resolution of school conflict in Colombia. - Miranda-Medina, Carlos F.; Albor-Chadid, Lourdes Isabel; Rodríguez-Burgos, Karla (Revista Pensamiento Americano)
Introduction: This article analyzes the effect of a social intervention program on conflict resolution skills and reasoning to observe school conflict in secondary school students from Barranquilla, Colombia. Method: A pre-experimental quantitative method is applied through a pre-test and post-test questionnaires to 81 students, 50.6 % women and 49.4 % men. Results: The social intervention program had as a result a great improvement in the reasoning of the students to observe the conflict with a change in means from 2.27 to 1.86, with Wilcoxon's W of 720, an effect size (EZ = .846) and a p value of .001, while there was a median improvement in the skills developed by the students for conflict resolution with M pretest = 2.43 to M posttest 2.17, W = 466, EZ = .566 and p value = .002. Conclusions: The reasoning to observe the conflict and the skills developed for the resolution of conflicts by the students can be stimulated through activities that train them in the recognition of conflicts and allow them to identify the tools they have to solve them. The results suggest that this type of intervention should be developed institutionally and permanently to modify the way students resolve conflicts and improve the school coexistence.